دور التخدير الموضعي في تسكين الألم التالي للعمليات القيصرية - الدالي, عصام; عبد الرحمن, أحمد; غنام, نوال (Latakia University Journal -Medical Sciences Series, 2019)
هدفت الدراسة إلى تحديد فعالية التشريب الموضعي لحواف الجرح بالبوبيفاكائين بعد العملية القيصرية في تسكين الألم. شملت الدراسة 214 حامل خروس أجري لهن عملية قيصرية تحت التخدير العام. تم تقسيم المريضات إلى مجموعتين:مجموعة A (104 مريضات) تم تسكين الألم بعد القيصرية بالتشريب الموضعي لحواف الجرح بالبوبيفاكائين 20 مل (0,1%).مجموعة B (110 مريضات) تم تسكين الألم بعد القيصرية بالديكلوفيناك العضلي 75 ملغ.فتبين أن شدة الألم مقاسة بالـ (Visual analogue scale) (VAS) بعد (2-4-6-8) ساعات بالترتيب:(2.46-2.21-2.08-2.28) مجموعة A مقابل (4.38-3.28-3.12-3.3) مجموعة B في أثناء الراحة و (4.21-3.36-3.1-3.7) مجموعة A مقابل (5.78-5.67-5.53-5.34) مجموعة B في أثناء الحركة أو السعال. وكانت الحاجة لإعطاء مسكن إضافي أقل في المجموعة A (7.69%) من المجموعة B (18.18%).بالنتيجة: تفوق التشريب الموضعي لحواف الجرح بالبوبيفاكائين على الديكلوفيناك في تسكين الألم بعد القيصرية. To assess the efficacy of subcutaneous wound infiltration with bupivacaine in relieving pain after cesarean delivery we studied 214 nulliparity pregnant women who underwent cesarean delivery under general anaesthesia. We divided the patients to two groups: Group A (104 patients) received wound infiltration with bupivacaine 20 ml (0,1%). Group B (110 patients) received 75 mg diclofenac intramuscular. We found that the pain level measured by visual analogue scale (VAS) after (2-4-6-8) hour in order: (2.46-2.21-2.08-2.28) group A (4.38-3.28-3.12-3.3) group B at rest. (4.21-3.36-3.1-3.7) group A (5.78-5.67-5.53-5.34) group B at movement or cough and the need of additional analgesia was less in group A (7.69%) than group B (18.18%). In conclusion: wound infiltration with bupivacaine was more effective than diclofenac in relieving pain after cesarean delivery.